‘God Protects Us’: Nationalism versus Religious representation in the US and Indonesian Presidential Speeches - Munandar, Aris (Celt: A Journal of Culture, English Language Teaching & Literature, 2023)
Presidential speech may reflect the cultural identity of the nation. This corpus-based research investigates the religiosity reflection in the U.S and Indonesian presidential speeches to reveal the underlying values. It built the corpus from the US presidential speeches (321,508 words) and the Indonesia presidential speeches (93,419 words) It applies Wordsmith 4.0 for the data mining. The findings show that both presidents used religious-related words, particularly ‘god’. The US president has used ‘god’ in fixed expressions ‘God bless you all’ and ‘May God protect our troops’, while the Indonesian president uses the word ‘god’ including its synonym in Arabic ‘Alloh’ in a wider variety of expressions such as ‘May god bless us all’, ‘May God protect us’, ‘the almighty God’, and ‘God’s help’ and ‘Bismillah’ (by the name of God), ‘Alhamdulillah’ (Praise be to Alloh), and ‘Insyaalloh’ (God willing). However, the use of ‘god’ in presidential speeches has different underlying values: the American president demonstrates strong nationalism, while the Indonesian president shows the strong religious side of the Indonesian people. The research concludes that the US president expresses religiosity in a more implicit manner, being in line with the self-reliant attitude of American society. On the contrary, the Indonesian president expresses religiosity in a very explicit manner, reflecting a god-dependent attitude in Indonesian society.